Nutritive Value of Important Fodder Species in Successional Grassland Ecosystem in Manipur - Thokchom, Amrabati; Khan, M R; Yadava, P S (International Journal of Ecology and Environmental Sciences, 2024)
Nutritive components such as crude protein, crude fibre, cellulose, hemicellulose, lignin, nitrogen, phosphorus and potassium, of important fodder plant species in successional grassland in Manipur have been evaluated throughout the year. The amount of crude protein and fibre varied from 2.38% (January) to 25.75% (May) and 25.20% (January) to 69.87% (July), respectively in different species. Cellulose, hemicellulose and lignin contents also ranged from 37.19% (March) to 60.42% (May), 19.89% (March) to 44.59% (September) and 4.28% (March) to 28.21% (January), respectively, in different species across the months. The highest nutritive value of plant species i.e., nitrogen, phosphorus and potassium content was found to be during the rainy months of July/September. Out of 13 fodder plant species, Desmodium triflorum exhibited highest content for crude protein and nitrogen, Fimbristylis dichotoma for crude fibre, and potassium, Arundinella setosa for cellulose, Bothriochloa intermedia for Hemicellulose, Dichanthium annulatum for lignin, Andropogon ascinodes for phosphorus during the study period. These species are more palatable in early vegetative stage and considered excellent nutritious fodders.